Pemulihan Identitas Naratif Korban Kekerasan Seksual : Sebuah Tinjauan Filsafat dan Teologi Kristen - Jessica Novia Layantara; David Tobing (Societas Dei: Jurnal Agama dan Masyarakat, 2021)
As traumatic events, sexual violence can paralyze victim’s identity so that the victim losing her capability as a human being. However , the identity of  sexual violence victims could be restored. The question needed to be answered in this article is: What makes it possible, philosophically and theologically, for a victim of sexual violence to be restored or transformed into a redeemed survivor? This article will attempt to answer the question from Paul Ricoeur's view of narrative identity as  a  framework, and Miroslav Volf's view of sacred memory in the history of salvation as the content of  the redeemed survivor identity. The thesis of this article is  about the recovery or the  changing  identity of the victim into a redeemed survivor that is possible through the reestablishment of  narrative identity which contains sacred memory in narrative paradigm of Christian salvation history.